OCT Imaging of Lid-Parallel Conjunctival Folds in Soft Contact Lens Wearers - Tapasztó, Beáta; Veres, Amarilla; Kosina-Hagyó, Krisztina; Somfai, Gábor Márk; Németh, János (Optometry and vision science, 2011)
To visualize, using Fourier-domain optical coherence tomography (FD-OCT), the alterations in lid-parallel conjunctival fold (LIPCOF) morphology in eyes with contact lenses and after their removal. One randomly selected eye of each of 24 volunteers with normal ocular surface status was examined using FD-OCT. The study group included 18 female and 6 male subjects, with a mean age of 28.9 years (range, 18-50 years). The presence, height, and number of conjunctival folds and the tear meniscus area were evaluated by FD-OCT, and the difference between "before and after lens removal" were analyzed by the Wilcoxon signed-rank test. To determine the coverage of the folds, the OCT-LIPCOF grading system was applied. Visualization of the folds was compared on linear and raster scans. The Spearman rank test was applied for correlations (SPSS 16.0; SPSS Inc., Chicago, MI). OCT scans were able to visualize and objectively describe the LIPCOF and its relation to the tear film in contact lens wearers. Raster scanning provided more information about the folds, but the measurements were easier to carry out on the single line scans. After removal of the contact lens, the height of the conjunctival folds significantly decreased (p < 0.001), and the tear meniscus area significantly increased (p = 0.017). The number of LIPCOF did not change (p = 0.971), but LIPCOF coverage by the tear film increased after lens' removal and resulted in changes in the OCT-LIPCOF grading (p < 0.001). FD-OCT could be a quick, non-invasive, quantitative method for the imaging of LIPCOF in contact lens patients. When grading LIPCOF, the mechanical forces of the lens and the tear meniscus changes caused by the lens should be taken into account as these factors influence results. Follow-up of the patients using the same methods is suggested with or without contact lenses.